المرأة في المغرب الأوسط خلال العهد الزياني (633-962ه/1235-1555م) قراءة في الحضور العسكري والسياسي - خلفات, مفتاح; عمروش, حسيبة (جامعة الوادي - University of Eloued, 2016)
تعتبر الدولة الزيانية واحدة من القوى السياسية التي قامت في بلاد المغرب الأوسط خلال الفترة الممتدة من (633-962ه/1235-1555م)، وكان لموقعها الجغرافي الوسطي وإمكانياتها الاقتصادية أثر في ازدياد الأطماع فيها من طرف القوى المجاورة ونعني بهم الحفصيين من الشرق والمرينيين من الغرب؛ زد على ذلك تمرد بعض القبائل العربية والبربرية على السلطة المركزية، وفي نهاية عهدها تعرضت لغارات النصارى الأسبان؛ كل هذه الظروف جعلت الدولة الزيانية وعاصمتها تلمسان مهددة في وجودها وأمنها واستقرارها. لكن وعلى الرغم من الصراع الطويل الذي شهدته الدولة على مرّ تاريخها خاصة ضد المرينيين؛ إلاّ أنّ ذلك لم يمنعها من فرض نفسها سياسيا وعسكريا وحضاريا، وذلك من خلال تضافر جهود مختلف الفعاليات الاجتماعية المنضوية تحت لواء هذه الدولة؛ ومن بينها المرأة التي كان لها حضورا خلال هذه الفترة حسبما تشير إليه بعض مصادر المرحلة؛ على الرغم من أنّ مهمة المرأة الأساسية هي رعاية شؤون الأسرة وتربية الأبناء بيد أنّ هذا لم يمنعها من المساهمة في شتى المجالات الأخرى السياسية والعسكرية والفكرية والاقتصادية وغيرها. والمأمول من هذه الورقة هو تسليط الضوء على دور المرأة في البناء الحضاري للدولة الزيانية، وذلك من خلال الوقوف على إسهاماتها في المجالات الحياتية وبخاصة في المجالين العسكري والسياسي. bstract : If we speak about the Zianists empire , we can say many things about this superpower , That emerged in the middel of Megreb country between the period of : (1235-1555 B C/633-962a- A D). This may be going back or pertaining to many factors according to hitorical studies. First of all , The geographical location that makes it squeezed between two tears , this created offensives and attacks from the Hafsists from the East and the Marrinians from the west in addition to these factors disabedience of few tribes Arabian and Barbarian tribes at the end of its age be confronted with the Spanish people. All these conditions contribute to make the Zianists power menaced about its existence and sedentation. But although this long conflict that exposed this nation during its histery against the Marrinians never handicapped it and make its assumption in political, military and civilization domains in the yard of Islamic Megreb, these ofcourse according to the great efforts of various sociable efficacies that work under this power among them we find a women that have a great existence and huge role during this period depending on how different studies were mentioned in spite of the fact that the role of women was limitted only on patronaging and educating children and takes care on its family but never handcapped or forbided her to make achievements and contributions in varuons fields, political, military, economical and ideational (intellectual). What is our objective in this paper is to have a deep look about the great role of women in the Zianist age and its contributions in different domains specially in military and political fields.
مقال
Keywords: العهد الزياني، المرأة الزيانية، تلمسان، الدور العسكري، المساهمة في المجال السياسي; AL ziani era – Woman Zianist – Military role – Contribution in politic field